Atrazine alters early sexual development of the South American silverside, Odontesthes bonariensis - Carriquiriborde, Pedro; Fernandino, Juan Ignacio; López, Carina Gabriela; De San Benito, Eduardo; Gutierrez-Villagomez, Juan Manuel; Cristos, Diego Sebastian; Trudeau, Vance L.; Somoza, Gustavo Manuel (Elsevier, 2023)
Atrazine (ATZ) is a frequent contaminant in freshwater ecosystems within agricultural regions. The capacity of this herbicide to interfere with the vertebrate endocrine system is broadly recognized, but the mechanisms and responses usually differ among species. In this study, ATZ effects on hypothalamus-pituitary-gonadal (HPG) axis key genes expression and early gonadal development were evaluated in Odontesthes bonariensis larvae waterborne exposed during the gonadal differentiation period. Fish were treated to 0, 0.7, 7.0, and 70 µg ATZ/L at 25 °C from the 2nd to 6th week after hatching (wah), and a group was kept in clean water until the 12th wah. Parallelly, a group was submitted to 0.05 µg/L of ethinylestradiol (EE2) as a positive estrogenic control. From each treatment, eight larvae were sampled at 6 wah for gene expression analysis and twelve larvae at 12 wah for phenotypic sex histological determination. The expression of gnrh1, lhb, fshb, and cyp19a1b was assessed in the head, and the ones of amha, 11βhsd2, and cyp19a1a in the trunk. Fish growth was significantly higher in fish exposed to 7 and 70 µg ATZ/L in the 6 wah, but the effect vanished at the 12 wah. The expression of lhb was upregulated in both sex larvae exposed from 7 µg ATZ/L. However, a dimorphic effect was induced on cyp19a1a expression at 70 µg ATZ/L, up or downregulating mRNA transcription in males and females, respectively. Delayed ovarian development and increased number of testicular germ cells were histologically observed from 7 to 70 µg ATZ/L, respectively, and a sex inversion (genotypic male to phenotypic female) was found in one larva at 70 µg ATZ/L. The lhb expression was also upregulated by EE2, but the cyp19a1a expression was not affected, and a complete male-to-female reversal was induced. Further, EE2 upregulated gnrh1 in females and cyp19a1b in both sexes, but it did not alter any assessed gene in the trunk. In conclusion, ATZ disrupted HPG axis physiology and normal gonadal development in O. bonariensis larvae at environmentally relevant concentrations. The responses to ATZ only partially overlapped and were less active when compared to the model estrogenic compound EE2. //Resumen: La atrazina (ATZ) es un contaminante frecuente en los ecosistemas de agua dulce dentro de las regiones agrícolas. La capacidad de este herbicida para interferir con el sistema endocrino de los vertebrados está ampliamente reconocida, pero los mecanismos y las respuestas suelen diferir entre especies. En este estudio, se evaluaron los efectos de ATZ en la expresión de genes clave del eje hipotálamo-pituitario-gonadal (HPG) y el desarrollo gonadal temprano en larvas de Odontesthes bonariensis expuestas al agua durante el período de diferenciación gonadal. Los peces se trataron con 0, 0,7, 7,0 y 70 µg ATZ/L a 25 °C desde la 2.ª a la 6.ª semana después de la eclosión (wah), y un grupo se mantuvo en agua limpia hasta el 12.º wah. Paralelamente, un grupo fue sometido a 0,05 µg/L de etinilestradiol (EE2) como control estrogénico positivo. De cada tratamiento, se tomaron muestras de ocho larvas a 6 wah para el análisis de expresión génica y doce larvas a 12 wah para la determinación histológica del sexo fenotípico. Se evaluó la expresión de gnrh1, lhb, fshb y cyp19a1b en la cabeza y de amha, 11βhsd2 y cyp19a1a en el tronco. El crecimiento de los peces fue significativamente mayor en los peces expuestos a 7 y 70 µg ATZ/L en el 6 wah, pero el efecto desapareció en el 12 wah. La expresión de lhb aumentó en larvas de ambos sexos expuestas a 7 µg ATZ/L. Sin embargo, se indujo un efecto dimórfico en la expresión de cyp19a1a a 70 µg ATZ/L, regulando hacia arriba o hacia abajo la transcripción del ARNm en machos y hembras, respectivamente. Se observó histológicamente un retraso en el desarrollo ovárico y un mayor número de células germinales testiculares de 7 a 70 µg ATZ/L, respectivamente, y se encontró una inversión sexual (genotípica de macho a fenotípica femenina) en una larva a 70 µg ATZ/L. EE2 también aumentó la expresión de lhb, pero la expresión de cyp19a1a no se vio afectada y se indujo una reversión completa de hombre a mujer. Además, EE2 aumentó gnrh1 en mujeres y cyp19a1b en ambos sexos, pero no alteró ningún gen evaluado en el tronco. En conclusión, ATZ interrumpió la fisiología del eje HPG y el desarrollo gonadal normal en larvas de O. bonariensis en concentraciones ambientalmente relevantes. Las respuestas a ATZ solo se superpusieron parcialmente y fueron menos activas en comparación con el compuesto estrogénico modelo EE2.